2020
DOI: 10.1056/nejmoa1911426
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Leaflet Motion after Transcatheter Aortic-Valve Replacement

Abstract: BACKGROUNDSubclinical leaflet thickening and reduced leaflet motion of bioprosthetic aortic valves have been documented by four-dimensional computed tomography (CT). Whether anticoagulation can reduce these phenomena after transcatheter aortic-valve replacement (TAVR) is not known. METHODSIn a substudy of a large randomized trial, we randomly assigned patients who had undergone successful TAVR and who did not have an indication for long-term anticoagulation to a rivaroxaban-based antithrombotic strategy (rivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(167 citation statements)
references
References 28 publications
4
158
0
5
Order By: Relevance
“…46 Interestingly, subclinical leaflet-motion, as potential surrogate marker for thrombotic valve alteration, was reduced under rivaroxaban as shown in an accompanying imaging study. 47 Similar findings were made in an earlier animal study that suggested that rivaroxaban might be superior to standard therapy after mechanical valve surgery in terms of valve thrombus and platelet deposition. 48 Unexpected results came also from the Re-Align study, that aimed to investigate dabigatran in patients after mechanical heart valve surgery.…”
Section: Factor Xa Inhibitorssupporting
confidence: 83%
“…46 Interestingly, subclinical leaflet-motion, as potential surrogate marker for thrombotic valve alteration, was reduced under rivaroxaban as shown in an accompanying imaging study. 47 Similar findings were made in an earlier animal study that suggested that rivaroxaban might be superior to standard therapy after mechanical valve surgery in terms of valve thrombus and platelet deposition. 48 Unexpected results came also from the Re-Align study, that aimed to investigate dabigatran in patients after mechanical heart valve surgery.…”
Section: Factor Xa Inhibitorssupporting
confidence: 83%
“…Recently, the GALILEO-4D sub-study demonstrated that dual pathway inhibition (rivaroxaban 10 mg plus ASA) is more effective than DAPT (ASA plus clopidogrel) in preventing subclinical leaflet abnormalities as documented using 4D CT. 107 However, these results should be cautiously interpreted due to the higher risk of adverse outcomes found with the rivaroxaban-based strategy in the parental trial. In conclusion, while European guidelines did not provide specific recommendations supporting anticoagulant pathways in patients without a coexisting indication for OAC, American guidelines were published at a time when new evidence from large registries and the AUREA and GALILEO trials that showed a definite increase in the bleeding rate without significant benefits with OAC, was not available.…”
Section: Patients Without a Coexisting Indication For Anticoagulationmentioning
confidence: 98%
“…The etiology of MR plays an important role in the therapy, particularly in old patients. In developed countries, the etiology of MR in geriatric patients is usually secondary [54,61,79,80]; in this clinical setting, the clinical benefit of surgery remains uncertain. The ESC Guidelines [79] provide no recommendations for the therapy of secondary MR, while the American Guidelines [80] propose individualized approaches.…”
Section: Valve Heart Diseasesmentioning
confidence: 99%
“…In developed countries, the etiology of MR in geriatric patients is usually secondary [54,61,79,80]; in this clinical setting, the clinical benefit of surgery remains uncertain. The ESC Guidelines [79] provide no recommendations for the therapy of secondary MR, while the American Guidelines [80] propose individualized approaches. Currently, mitral valve repair (MVR) is the generally accepted "gold standard" treatment for degenerative MR [81][82][83], while surgical mitral valve replacement (SMVR) is indicated only in cases where the expected clinical improvements exceed the increased operative risk associated with aging and comorbidities [80][81][82][83][84][85].…”
Section: Valve Heart Diseasesmentioning
confidence: 99%